Germination of Terminalia Bellerica (gaertn.) Roxb. as Affected by Various Potting Media - Patel, V.S.; Patil, N.S.; Tandel, M.B. (Indian Forester, 2013)
The present investigation on germination of Terminalia bellerica (Gaertn.) Roxb. as affected by various potting media of sand, farm yard manure (FYM), clay soil, loamy soil, vermiculite and coco-peat. There were 18 different combinations of potting mixtures. The experiment was conducted in completely randomized block design with three replications. The effect of potting mixtures on percentage of germination, days taken for complete germination, root length, shoot length, number of leaves per plant, plant fresh weight and plant dry weight after two months of seed sowing were examined. Among all these mixtures, sand, FYM and loamy soil in 1:2:1 ratio was recorded best in most of the growth parameters.